ANALISIS TAX AVOIDANCE DITINJAU DARI KARAKTERISTIK PERUSAHAAN - Retno Sundari; Anisa Kusumawardani (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to examine and analyze the influence of company characteristics, namely profitability, leverage, sales growth, and firm size, on tax avoidance practices. The population of this research consists of manufacturing companies listed on Indonesia Stock Exchange during the 2021–2024 period. The sampling process employed a purposive sampling technique, resulting in 74 companies with a total of 296 observation data that met the research criteria. The study applied a quantitative approach using secondary data obtained from annual financial reports. Data were analyzed through multiple linear regression using the SPSS version 25 software. The findings indicate that profitability, sales growth, and firm size negatively affect tax avoidance, while leverage shows a positive effect on tax avoidance. Furthermore, the coefficient of determination test produced an adjusted R-square value of 0.298, suggesting that the independent variables included in this study have limited explanatory power in predicting tax avoidance practices. The results imply that corporate financial characteristics contribute differently to managerial decisions related to tax strategies and corporate tax planning